The Effect of Taxifolin on Cisplatin-Induced Pulmonary Damage in Rats: A Biochemical and Histopathological Evaluation - Edhem Unver; Mustafa Tosun; Hasan Olmez; Mehmet Kuzucu; Ferda Keskin Cimen; Zeynep Suleyman (Mediators of Inflammation)
The effect of taxifolin on cisplatin-induced oxidative pulmonary damage was investigated biochemically and histopathologically in male albino Wistar rats. There were four groups, with six animals in each group: 50 mg/kg of taxifolin plus 2.5 mg/kg of cisplatin (TC) group, 2.5 mg/kg of cisplatin only (CIS) group, 50 mg/kg of taxifolin only (TG) group, and a healthy control group (HG). In terms of the experimental procedure, the animals in the TC and TG groups were first treated via oral gavage. The CIS and HG groups received distilled water as solvent, respectively. One hour later, the TC and CIS groups received cisplatin at a dose of 2.5 mg/kg (injected intraperitoneally). Taxifolin, cisplatin, and the distilled water were administered at the indicated dose and volume, using the same method daily for 14 d. At the end of this period, the animals were killed with a high dosage of thiopental anaesthesia (50 mg/kg). Blood and lung tissue samples were taken for biochemical (malondialdehyde (MDA), myeloperoxidase (MPO), total glutathione (tGSH), and 8-hydroxy-2 deoxyguanosine (8-OHdG)) analyses and histopathological examinations. The biochemical and histopathological results in the TC and HG groups were then compared with those in the CIS group. Cisplatin increased the levels of MDA, myeloperoxidase, and 8-OHdG, a marker of oxidative DNA damage, and reduced the amount of tGSH in the lung tissue. Moreover, severe alveolar damage, including oedema and extensive alveolar septal fibrosis, in addition to infiltration of polymorphic nuclear leucocytes and haemorrhagic foci, was observed in the CIS group. These histopathological findings demonstrate that taxifolin provides protection against pulmonary oxidative stress by preventing increases in oxidant parameters and decreases in antioxidants.